Income convergence among Brazilian states after the economic openness - Maria Alice Móz Christofoletti; Humberto Francisco Silva Spolador (European Regional Science Association (ERSA), 2010)
This paper expands the analysis developed by Ellery Jr. (1994), who estimated the income convergence among Brazilian states from 1970 to 1990. The methodology is based on the convergence model proposed by Barro and Sala-i-Martin (1992) and is applied to test both the beta-convergence and the sigma-convergence. For the period after 1990, and sub-periods, the effects of educational level (used as a proxy for human capital), and international trade on the increase of income states were estimated. The preliminary results show that even after the economic openness in 1990s, the income convergence process has not changed compared to the first period previously analyzed (1970-1990) among the 27 Brazilian states and this process has been still ongoing (0.79% per year) to the recent years.
Keywords: 330; convergence; GDP per capita; Brazilian states